Contrast enhancement for Ziehl-Neelsen tissue slide images using linear stretching and histogram equalization technique - Osman, M.K.; Mashor, Mohd. Yusof, Prof. Dr.; Saad, Z.; Jaafar, H. (IEEE, 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/